An analytical study of sickle cell anemia incidence in the tribal population of eastern Gujarat - Niyati Harshadkumar Zaveri; Shivaji Dnyandeo Patil; Mohabatsinh Baria; Amrut Arun Swami; Rutvi Dilipbhai Katakia; Rahul Tahilramani (Journal of Family Medicine and Primary Care)
This study explored sickle cell disease (SCD) in the tribal population of Eastern Gujarat, India. The objectives included determining the incidence and gender-wise distribution of SCD cases. A hospital-based analytical study was conducted with 600 tribal participants. Data were gathered from medical records between June 1 and June 27, 2019. Ethical approval and participant consent were obtained. The study included patients diagnosed with SCD and excluded those who had undergone surgery, were females in their menstrual cycle, or were non-SCD patients. Data analysis was performed using SPSS 22.0 software. The highest incidence of SCD was observed in males aged 10 years–20 years and females aged 21 years–30 years. In whole study population, the incidence was 25.67%. Significant differences (P < 0.05) were found between male and female patients in red blood cell (RBC) count, hemoglobin (Hb) levels, white blood cell (WBC) count, mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), and packed cell volume (PCV). SCD patients showed lower RBC count, Hb concentration, PCV, and RBC indices but higher WBC counts. Significant gender differences were noted in several parameters. Due to limitations in data recording, mortality could not be thoroughly assessed. The study indicates that malnutrition, stemming from poverty, is a concern, and balanced diets are essential for reducing the incidence and morbidity of SCD.